Sample size estimation for health and social science researchers: The principles and considerations for different study designs - Bolarinwa, Oladimeji (The Nigerian postgraduate medical journal, 2020)
Sample size is one of the important considerations at the planning phase of a research proposal, but researchers are often faced with challenges of estimating valid sample size. Many researchers frequently use inadequate sample size and this invariably introduces errors into the final findings. Many reviews on sample size estimation have focused more on specific study designs which often present technical equations and formula that are boring to statistically naïve health researchers. Therefore, this compendium reviews all the common sample size estimation formula in social science and health research with the aim of providing basic guidelines and principles to achieve valid sample size estimation. The simplification of the sample size formula and detailed explanation in this review will demystify the difficulties many students as well as some researchers have with statistical formulae for sample size estimation.